Development of Autocad E-Module Teaching Materials for Simulation Learning Subjects and Digital Communication in Macromedia Flash-Based Vocational High Schools - Fikri Tri Handoko Megbel; Tuti Iriani; Arris Maulana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to create teaching materials in the form of AutoCAD e-modules for learning simulations and digital communication in Macromedia Flash-based vocational schools. This research was carried out at SMK Negeri 56 North Jakarta for 5 months using an R&D model with a 4D model and using non-test instruments in the form of observations and questionnaires with a 1-5 Likert scale with a total of 40 respondents of Class X Digital Simulation and Communication, 2 experts media, 2 material experts, and 2 teachers. The data analysis technique used is quantitative descriptive analysis. The results show that the learning module is categorized as